2013
DOI: 10.1371/journal.pone.0057517
|View full text |Cite
|
Sign up to set email alerts
|

The PPE Domain of PPE17 Is Responsible for Its Surface Localization and Can Be Used to Express Heterologous Proteins on the Mycobacterial Surface

Abstract: PPE represent a peculiar family of mycobacterial proteins characterized by a 180 aminoacids conserved N-terminal domain. Several PPE genes are co-transcribed with a gene encoding for a protein belonging to another family of mycobacterial specific proteins named PE. Only one PE-PPE couple has been extensively characterized so far (PE25-PPE41) and it was shown that these two proteins form a heterodimer and that this interaction is essential for PPE41 stability and translocation through the mycobacterial cell wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…On the basis of these observations, it has been proposed that these PE and PPE proteins are exported as folded heterodimers in M. tuberculosis (28, 32) with their final localization either at the cell surface of M. tuberculosis and/or in the culture medium (33). Flow cytometry experiments showed that PPE36 is a surface-accessible protein consistent with previous observations for several other PPE proteins (34, 35). PPE36 is exclusively associated with membranes in subcellular fractionation experiments in contrast to PPE62 and Rv0265c.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…On the basis of these observations, it has been proposed that these PE and PPE proteins are exported as folded heterodimers in M. tuberculosis (28, 32) with their final localization either at the cell surface of M. tuberculosis and/or in the culture medium (33). Flow cytometry experiments showed that PPE36 is a surface-accessible protein consistent with previous observations for several other PPE proteins (34, 35). PPE36 is exclusively associated with membranes in subcellular fractionation experiments in contrast to PPE62 and Rv0265c.…”
Section: Discussionsupporting
confidence: 89%
“…It is also unknown whether PPE36 requires PE22 for heme binding and/or uptake. PPE17 is a PPE protein that does not require its cognate PE proteins for stability and surface localization (35). Further experiments are needed to examine whether this is the case for PPE36.…”
Section: Discussionmentioning
confidence: 99%
“…Since some PE and PPE proteins are known to localize to the mycobacterial cell wall (3,7,8,34,36), we predicted that overexpression of pe19 contributes to stress sensitivity by altering the permeability of the cell envelope. To test this hypothesis, we used an ethidium bromide uptake assay which measures the in- FIG 7 ⌬ppe25-ppe26 and ⌬pe32-ppe65 deletions do not suppress sensitivity of the ⌬pstA1 mutant to acidic pH stress.…”
Section: Resultsmentioning
confidence: 99%
“…Since many PE and PPE proteins that have been characterized to date are localized to the cell wall (3,7,8,(34)(35)(36), we predicted that the aberrant overexpression of these proteins would sensitize M. tuberculosis to stress. We demonstrate that the overexpression of the PE protein PE19, which consists of only a 99-amino-acid PE domain, causes sensitivity to specific cell wall and oxidative stress conditions in vitro and to NOS2-independent host immune responses in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation